Entrepreneurship Programs in Developing Countries : A Meta Regression Analysis - Cho, Yoonyoung; Honorati, Maddalena (World Bank, Washington, DC, 2013)
This paper provides a synthetic and systematic review on the effectiveness of various entrepreneurship programs in developing countries. It adopts a meta-regression analysis using 37 impact evaluation studies that were in the public domain by March 2012, and draws out several lessons on the design of the programs. The paper observes wide variation in program effectiveness across different interventions depending on outcomes, types of beneficiaries, and country context. Overall, entrepreneurship programs have a positive and large impact for youth and on business knowledge and practice, but no immediate translation into business set-up and expansion or increased income. At a disaggregate level by outcome groups, providing a package of training and financing is more effective for labor activities. In addition, financing support appears more effective for women and business training for existing entrepreneurs than other interventions to improve business performance.